Narrative, Political - Hartley, John (John Wiley & Sons, 2015)
This series of newly commissioned, subdisciplinary international encyclopedias of communication builds on the success of the existing 12-volume Blackwell/ ICAInternational Encyclopedia of Communication (Donsbach, 2008) and is closely ...